Cost-effectiveness of the New Zealand diabetes in pregnancy guideline screening recommendations. Issue 6 (22nd June 2015) - Coop, Catherine; Edlin, Richard; Brown, Julie; Farquhar, Cindy
Abstract : Objective: To compare the cost-effectiveness of 2 possible screening strategies for gestational diabetes mellitus (GDM) from the perspective of the New Zealand health system, developed as part of a gestational diabetes guideline. Design: A decision analytic model was built comparing 2-step screening (glycated haemoglobin (HbA1c) test at first booking and a 2 h 75 g oral glucose tolerance test (OGTT) as a single test at 24–28 weeks) with 3-step screening (HbA1c test at first booking and a 1 h glucose challenge test (GCT) followed by a 2 h 75 g OGTT when indicated from 24–28 weeks) using a 9-month time horizon. Setting: A hypothetical cohort of 62 000 pregnant women in New Zealand. Methods: Probabilities, costs and benefits were derived from the literature, and supplementary data was obtained from National Women's Annual Clinical Reports. Main outcome measures, screening and treatment costs (NZ$2013) and effect on health outcomes (incidence of complications). Results: The total cost for both strategies under baseline assumptions shows that the 2-step screening strategy would cost NZ$1.38 m more than the 3-step screening strategy overall. The additional cost per case detected was NZ$12 460 per case. The model found that the 2-step screening strategy identifies 12 more women with diabetes and 111 more women with GDM when compared against the 3-step screening strategy. We assessed the effect of changing the sensitivity and specificity of the OGTT. The baseline model assumed that the 2 h 75 g OGTT has a sensitivity and specificity of 95%. The 2-step strategy becomes more cost-effective when the diagnostic accuracy measures are improved. Conclusions: Adopting a 2-step strategy would moderately increase the number of GDM cases detected at the same time as moderately increasing the number of women with false negatives at a significant cost to the health system. Further evidence on the benefits of the 2 different approaches would be welcome.